The Chromatin Remodeling Protein BRG1 Regulates SREBP Maturation by Activating SCAP Transcription in Hepatocytes - Kong, Ming; Zhu, Yuwen; Shao, Jing; Fan, Zhiwen; Xu, Yong (Frontiers in Cell and Developmental Biology, 2021)
Sterol response element binding protein (SREBP) is a master regulator of cellular lipogenesis. One key step in the regulation of SREBP activity is its sequential cleavage and trans-location by several different proteinases including SREBP cleavage activating protein (SCAP). We have previously reported that Brahma related gene 1 (BRG1) directly interacts with SREBP1c and SREBP2 to activate pro-lipogenic transcription in hepatocytes. We report here that BRG1 deficiency resulted in reduced processing and nuclear accumulation of SREBP in the murine livers in two different models of nonalcoholic steatohepatitis (NASH). Exposure of hepatocytes to lipopolysaccharide (LPS) and palmitate (PA) promoted SREBP accumulation in the nucleus whereas BRG1 knockdown or inhibition blocked SREBP maturation. Further analysis revealed that BRG1 played an essential role in the regulation of SCAP expression. Mechanistically, BRG1 interacted with Sp1 and directly bound to the SCAP promoter to activate SCAP transcription. Forced expression of exogenous SCAP partially rescued the deficiency in the expression of SREBP target genes in BRG1-null hepatocytes. In conclusion, our data uncover a novel mechanism by which BRG1 contributes to SREBP-dependent lipid metabolism.